Analisis Yuridis Peran Dan Kedudukan Korban Berdasarkan Undang-Undang No. 26 Tahun 2000 Tentang Pengadilan Hak Asasi Manusia (Studi Kasus Pelanggaran HAM Berat Di Wamena 2003) - Amar, Rezie Dava; Sinaga, Sesilia Faska Tiara Ernawati; Endiansyah, Jesicka Aurora; Destyana, Virgina; Priyana, Puti (Peneliti.net, 2024)
The problem that the author raises is the role of victims in cases of serious human rights violations in Wamena 2003, and what is the position and form of legal protection according to Law Number 26 of 2000 concerning Human Rights Courts. The research method used is normative juridical using secondary data and through statute approach, conceptual approach and case approach. The results and conclusions of this research are that the human rights problems in Wamena in 2003 were serious violations of human rights as regulated in Article 7 letter b and Article 9 of Law Number 26 of 2000 concerning Human Rights Courts. In the occurrence of human rights crimes in Wamena, the victim actually played a role, although the victim's role here is passive, the victim played a functional role in the occurrence of the crime. The position of victims and the form of legal protection for victims in Law Number 26 of 2000 concerning Human Rights Courts is confirmed in Articles 34-35. In accordance with the provisions of Article 35 paragraph (3), the Government then issued Government Regulation Number 3 of 2002 concerning Compensation, Restitution and Rehabilitation for Victims of Serious Human Rights Violations.